DEVELOPMENT OF AUGMENTED REALITY-BASED FLASHCARD MEDIA TO IMPROVE ELEMENTARY SCHOOL STUDENTS' ARABIC SPEAKING SKILLS - Mustofa, Ady Muh. Zainul; Al Qorin, Amami Shofiya; Suhanda, Imron; Fahreza, Muhammad Marsal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an Augmented Reality (AR)-based flashcard learning media to enhance the arabic speaking skills (maharah kalam) of students at SDIT As-Syifa Al Inayah 6 Kota Jambi. The ADDIE model was employed as the development framework, consisting of analysis, design, development, implementation, and evaluation stages. The analysis stage revealed that students require interactive-visual media to support vocabulary comprehension and build speaking confidence. During the design and development phases, the AR flashcards were created by integrating images, 3D animations, and pronunciation audio. Expert validation results indicated a high level of feasibility, with a percentage 90%. Implementation with a small student group demonstrated a significant improvement in vocabulary mastery, pronunciation accuracy, and the ability to construct simple sentences. Summative evaluation confirmed that AR media fosters a more active, communicative, and engaging learning environment. Overall, AR flashcards proved to be effective in enhancing speaking skills and serve as an innovative alternative for teaching Arabic at the elementary school level.